Answer:
is to be added to make
a perfect square trinomial as ![(x+\frac{1}{3})^{2}](https://tex.z-dn.net/?f=%28x%2B%5Cfrac%7B1%7D%7B3%7D%29%5E%7B2%7D)
Step-by-step explanation:
Given :
We have to find what can be added to
to form a perfect square trinomial.
Perfect square trinomial is of the form ![(a+b)^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2)
Consider the given expression
Using algebraic identity
,
Comparing , we get, a = x ......(1)
![2ab=\frac{2}{3}x](https://tex.z-dn.net/?f=2ab%3D%5Cfrac%7B2%7D%7B3%7Dx)
Uisng (1) , we get,
![2b=\frac{2}{3} \\\\ \Rightarrow b=\frac{1}{3}](https://tex.z-dn.net/?f=2b%3D%5Cfrac%7B2%7D%7B3%7D%20%5C%5C%5C%5C%20%5CRightarrow%20b%3D%5Cfrac%7B1%7D%7B3%7D)
To make it a perfect square trinomial we need to add
term
![b^2=\frac{1}{9}](https://tex.z-dn.net/?f=b%5E2%3D%5Cfrac%7B1%7D%7B9%7D)
Thus,
is to be added to make
a perfect square trinomial as ![(x+\frac{1}{3})^{2}](https://tex.z-dn.net/?f=%28x%2B%5Cfrac%7B1%7D%7B3%7D%29%5E%7B2%7D)